Landscape and territorial identity of the natural, rural and urban environment of Jumilla (Murcia, SE Spain) - Sánchez-Sánchez, Miguel Ángel; Belmonte-Serrato, Francisco; Ballesteros Pelegrín, Gustavo (M+A. Revista Electrónica de Medioambiente, 2017)
The municipality of Jumilla located in the Region of Murcia, has a territory that houses significant elements, the product of a long historical process, which has led to the existence of a unique territory. Through the landscapes, reflection and character of the territory, one can deepen in a better knowledge of the territorial identity of Jumilla. A better knowledge will allow facing new future challenges, taking advantage of those elements and / or processes that can not be delocalized, because they are endemic, in particular, that agricultural tradition associated with the cultivation of the vine and the production of wine. Through the study, analysis and assessment of landscapes, it helps to define the cultural identity of Jumilla. Its main objective is to determine the dominant landscapes of the municipality of Jumilla and elements that may contribute to its territorial identity. For this, an adapted template is used as reference, where elements of the landscape to be analyzed and evaluated are described.